(untitled) (Homiletic, 2024)
This article argues that Henry Ward Beecher’s use of imagination in preaching serves as a significant contribution to the field of homiletics. A renowned pastor and three-time lecturer at Yale’s distinguished preaching series, Beecher relied on his extensive creativity to not only shape the contours of his sermons, but also to impact a nation in the throes of Civil War. Though not always appreciated, Beecher models the need for, and practice of, imagination in Christian pulpits.